1994
DOI: 10.1037/0097-7403.20.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Internal clock and memory processes in animal timing.

Abstract: Temporal control of behavior was investigated within the framework of an internal clock model. Pigeons were exposed to signaled fixed-interval 30-s trials mixed with extended unreinforced (baseline) trials. On unreinforced break trials, the signal was interrupted for a period of time after trial onset. In Experiment 1, comparisons between the peak time obtained on baseline and on break trials produced peak time shifts that were longer than those expected if the clock had stopped during the break but shorter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 33 publications
(78 reference statements)
4
89
1
2
Order By: Relevance
“…Roberts, 1981)-a response rule called stop- Gibbon et al, 1984) proposed that the pacemaker is connected to the accumulator by means of a putative switch, that is closed during the to-be-timed signal and open during the gap, thus allowing, or not, pulse accumulation. In contrast to rats, birds tend to restart the entire timing process after the gap, a rule called reset (Bateson and Kacelnik, 1998;Brodbeck et al, 1998;Cabeza de Vaca et al, 1994;W. A. Roberts et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roberts, 1981)-a response rule called stop- Gibbon et al, 1984) proposed that the pacemaker is connected to the accumulator by means of a putative switch, that is closed during the to-be-timed signal and open during the gap, thus allowing, or not, pulse accumulation. In contrast to rats, birds tend to restart the entire timing process after the gap, a rule called reset (Bateson and Kacelnik, 1998;Brodbeck et al, 1998;Cabeza de Vaca et al, 1994;W. A. Roberts et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…A. Roberts et al, 1989). To acount for both the stop and reset behavior, Cabeza de Vaca et al (1994) proposed that subjective time-stored in working memory-decays passively during the gap. Moreover, to account for the fact that pigeons tend to stop when the gap is dissimilar from the inter-trial interval (ITI), Zentall and colleagues (Kaiser et al, 2002;Sherburne et al, 1998) proposed that subjects may perceive the gap as an ambiguous, ITI-like event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After each bout of cooing, a pause of 500 ms occurred where no vocalization could be heard. Previous timing studies with pigeons and blackcapped chickadees have indicated that the internal clock is partially reset when a gap is encountered (Roberts et al, 1989;Cabeza de Vaca et al, 1994;Brodbeck et al, 1998). Although the gaps in these studies were substantially greater than 500 ms, it is possible that the brief pauses in the cooing stimulus may play a role in timing.…”
Section: Methodsmentioning
confidence: 88%
“…This timing difference could have been the result of natural pauses (gaps) in the cooing stimulus (Roberts et al, 1989;Cabeza de Vaca et al, 1994;Brodbeck et al, 1998). The purpose of the second set of tests was to determine whether the initial timing difference was the result of brief pauses in the cooing signal.…”
Section: Discussionmentioning
confidence: 99%